"Am I Chinese before I am a woman or am I a woman first?": Gender and Racial Melancholia in Brian Castro's The Garden Book. Issue 4 (2nd October 2022) - Zhuoling, Tian
ABSTRACT: The female protagonist in The Garden Book is the site of both imaginary and symbolic fantasy, as well as the melancholic real. In this article, I explore how a Chinese-Australian woman comes to inhabit a melancholic position of racial and gendered difference, and how Brian Castro, through his portrayal, deconstructs identity markers such as race, gender and nation. Born and raised in Australia, Swan is a legitimate Australian citizen. However, her Asian appearance and gender identity compromise her legitimacy as a subject of the Australian nation-state. The Chinese-Australian woman as image and fantasy of Oriental femininity becomes a spectre, an "Other" haunting the history and memory of white Australia. Castro's writing shows how racial and sexual difference constructs and deconstructs identity, individual as well as national. In Swan's case, gendered racialisation derived from imperialism disrupts the coherence of national citizenship. Reading the character of Swan as presented through the eyes of the men in her life, this article provides an alternative site where what is excluded, disavowed and lost in white Australia becomes visible. Swan's racial and gendered melancholia allows us to see imperial violence and colonial eroticism at the heart of cultural essentialism and nationalism.